Sustained transmission of high-level azithromycin-resistant Neisseria gonorrhoeae in England: an observational study. Issue 5 (May 2018) - Fifer, Helen; Cole, Michelle; Hughes, Gwenda; Padfield, Simon; Smolarchuk, Christa; Woodford, Neil; Wensley, Adrian; Mustafa, Nazim; Schaefer, Ulf; Myers, Richard; Templeton, Kate; Shepherd, Jill; et al.
Summary: Background: Between Nov 3, 2014, and Feb 24, 2017, 70 cases of high-level azithromycin-resistant (HL-AziR; minimum inhibitory concentration [MIC] ≥256 mg/L) Neisseria gonorrhoeae were reported from across England. Whole-genome sequencing was done to investigate this outbreak to determine whether the ongoing outbreak represented clonal spread of an HL-AziR N gonorrhoeae strain identified in Leeds. We also wanted to elucidate the molecular mechanisms of azithromycin resistance in N gonorrhoeae in the UK. Methods: In this observational study, whole-genome sequencing was done on the HL-AziR N gonorrhoeae isolates from England. As comparators, 110 isolates from the UK and Ireland with a range of azithromycin MICs were also sequenced, including eight isolates from Scotland with azithromycin MICs ranging from 0·12 mg/L to 1·00 mg/L that were N gonorrhoeae multi-antigen sequence type 9768 (ST9768), which was the sequence type initially responsible for the outbreak. The presence of mutations or genes associated with azithromycin resistance was also investigated. Findings: 37 of the 60 HL-AziR isolates from England belonged to ST9768, and were genetically similar (mean 4·3 single-nucleotide polymorphisms). A 2059A→G mutation was detected in three or all four alleles of the 23S rRNA gene. Five susceptible ST9768 isolates had one mutated 23S rRNA allele and one low-level resistant ST9768 isolate had two mutated alleles. Interpretation: Sustained transmission of a successful HL-AziR clone was seen across England. Mutation 2059A→G was found in isolates with lower azithromycin MICs. Azithromycin exposure might have provided the selection pressure for one or two mutated copies of the 23S rRNA gene to recombine with wild-type copies, leading to three or four mutated copies and the HL-AziR phenotype. HL-AziR could emerge in isolates with low azithromycin MICs and eliminate the effectiveness of azithromycin as part of dual therapy for the treatment of gonorrhoea. Funding: Public Health England.